Perancangan Game Edukasi “The Legend of Al-Khawarizmi” sebagai Alat Bantu Pembelajaran Mahasiswa Berkebutuhan Khusus - Iqbal Yusuf Fadillah; Bella Hardiyana; Rani Puspita Dhaniawaty (Jurnal Pendidikan Kebutuhan Khusus, 2021)
The purpose of this research is to produce educational games that can support learning for students with special needs. The selection of game media is expected to attract students with special needs to participate in the learning process organized by the university because in the game itself there are several animations, interactions, and challenges that can change the learning atmosphere to be fun. Currently, games are not only for entertainment but games can also function as a means of learning. The game as a learning tool is not a new concept, this concept emerged along with the emergence of various kinds of games. The genre of this game is RPG (Role-playing Game). Until in the end, this game comes as an interactive and communicative learning media for students with special needs and can make it easier for lecturers or teaching staff to convey the material presented.